Stimulasi Molting pada Kepiting Kelapa (Birgus latro, Linnaeus 1767) dengan Pakan Buatan Diperkaya Fitoekdisteroid - Mufti Abdul Murhum; Budi Wahono; Sri Endah Widiyanti (Jurnal Sumberdaya Akuatik Indopasifik, 2019)
One of the problems in coconut crab cultivation is its slow growth. Artificial feed can be an alternative in the development of coconut crab cultivation (B. latro). The purpose of this research is to analyze the formula of artificial feed that gives the best stimulation on the growth of coconut crab. Three artificial feed with protein content A (20%), B (25%) and C (27%) and D (fresh coconut meat) as control. During the study, the test crabs were individually maintained in confinement containers that were specially designed to be as comfortable as in nature and not loose out. The results of the study, formulated feed can be eaten by crab test with the highest molting percentage in crab test treated with artificial feed of formula C 100%, followed by treatment A or B each 75% and D 25%. In conclusion that the feed made can be eaten and allegedly able to induce molting in coconut crabs.